238 U, 232 Th and 40 K in wheat flour samples of Iraq markets - A. A. (Ukrainian Food Journal, 2014)
Introduction. Wheat flour is a nutritious type of food that is widely consumed by various age groups in Iraq. This study investigates the presence of long-lived gamma emitters in different type of wheat flour in Iraqi market. Materials and methods. Uranium ( 238 U), Thorium ( 232 Th) and Potassium ( 40 K) specific activity in (Bq/kg) were measured in (12) different types of wheat flours that are available in Iraqi markets. The gamma spectrometry method with a NaI(Tl) detector has been used for radiometric measurements. Also in this study we have calculated the internal hazard index, radium equivalent and absorbed dose rate in all samples. Results and discussion. It is found that the specific activity in wheat flour samples were varied from (1.086±0.0866) Bq/kg to (12.532±2.026) Bq/kg with an average (6.6025) Bq/kg for 238 U, For 232 Th From (0.126±0.066) Bq/kg to (4.298±0.388) Bq/kg with an average (1.9465)Bq/kg and for 40 K from (41.842±5.875) Bq/kg to (264.729±3.843) Bq/kg with an average (133.097) Bq/kg. Also, it is found that the radium equivalent and the internal hazard index in wheat flour samples ranged from (3.4031) Bq/kg to (35.1523) Bq/kg with an average (19.6346) Bq/kg and from (0.0091) to (0.1219) with an average (0.0708) respectively. Conclusion. This study prove that the natural radioactivity and radiation hazard indices were lower than the safe.